Impunity:In the Search of a Socio-Legal Concept. Elucidations from a State Crime Case Study - Umana, Camilo (Université d'Ottawa / University of Ottawa, 2017)
In the contemporary world, the fight against impunity has become a fundamental political claim, a social goal and a main concern for human rights movements. However, it is unclear how we can delimit this fight, what are its aims and, ultimately, the remedies it proposes to overcome impunity. The academic studies and human rights mechanisms referring to this issue are not sufficiently clarifying. They often lack clear theoretical distinctions and stable empirical observations. Moreover, in social discourses impunity is employed with extremely vague connotations. This research addresses this lacuna, offering a conceptualization and characterization of impunity from a socio-legal perspective. With this purpose in mind, this work develops an analysis of impunity through the study of a particular kind of criminality. The study of state crime provides a prolific perspective for the analysis of the phenomenon of impunity, allowing to visualize the constitution of different blockages against the autonomous operation of the criminal justice. Particularly, this research studies an event of enforced disappearance initiated at the siege of the Colombian Palace of Justice in 1985, through a reconstruction focused on the perspective of the victims using a combination of qualitative methods. This field work, alongside different explorations of the sociological, human rights and criminological state of art of impunity, provides a sociological reflection on the concept of impunity. In the end, taking into account the problematization of the concept and its uses in social discourses, this work proposes a conceptualization apt for overcoming the vagueness of the definition of impunity as well as allowing a delimitation of the fight against it, leaving space for possible innovations on the penal rationality and possibly reinforcing a human rights agenda, concerned with the escalation of repression through punishment and committed with the restoration of social links and the victims’ rights.
Keywords: Colombia; State crime; Criminal justice; Impunity; Crime; Case study